Chemical mechanical planarization slurry processing technique and system and method for using same to polish substrates - Patents.com
Patent Information
- Application Number
- JP2024546406
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-28
- Filing Date
- 2022-08-12
- Publication Date
- 2025-03-11
Smart Images

Figure 2025506433000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 63 / 335,783 (filed April 28, 2022) and is a continuation-in-part of International Application No. PCT / US22 / 15424 (filed February 7, 2022). This international patent application claims priority to U.S. Provisional Patent Application No. 63 / 149,733, filed February 16, 2021, U.S. Provisional Patent Application No. 63 / 150,683, filed February 18, 2021, U.S. Provisional Patent Application No. 63 / 165,444, filed March 24, 2021, U.S. Provisional Patent Application No. 63 / 186,343, filed May 10, 2021, U.S. Provisional Patent Application No. 63 / 188,305, filed May 13, 2021, and U.S. Provisional Patent Application No. 63 / 211,083, filed June 16, 2021, each of which is incorporated by reference in its entirety herein.
[0002] This application is related to U.S. Pat. No. 8,197,306, U.S. Pat. No. 8,845,395, U.S. Pat. No. 9,296,088, Korean Pat. No. 10-1394745, Japanese Pat. No. 5,574,597, and Taiwanese Pat. No. 1,486,233, each of which is incorporated herein by reference in its entirety.
[0003] FIELD OF THEINVENTION The present disclosure relates generally to chemical mechanical planarization (CMP) for semiconductor manufacturing processes. More specifically, the present disclosure relates to enhancements to slurry formulations, and apparatus and processes for polishing substrates such as semiconductor wafers. [Background technology]
[0004] Chemical mechanical planarization (CMP) is a part of the semiconductor manufacturing process that performs material removal on a substrate, e.g., a wafer, during integrated circuit (IC) manufacturing to planarize metal, polysilicon, and / or dielectric layers. CMP performs chemical reactions and applies mechanical forces by applying abrasive particles to remove metal deposits and the like that form the layers.
[0005] The CMP process generally involves the use of a slurry distribution system, which includes an apparatus that delivers a source of slurry to a polishing pad to apply a combination of chemicals and abrasive particles to a rotary substrate polisher on which a wafer is positioned. Without a proper system, the type and properties of the slurry material, and the manner in which the slurry is applied, can result in lower material removal rates, greater than necessary slurry consumption, and undesirable surface scratches or other defects on the wafer.
[0006] The discussion above is merely provided for general background information and is not intended to be used as an aid in determining the scope of the claimed subject matter. Summary of the Invention
[0007] In one aspect, the inventive concept provides a chemical mechanical planarization (CMP) method comprising the steps of providing a source of CMP slurry, modifying the source of CMP slurry to form a modified CMP slurry by supplying at least one source of mechanical wave energy or electromagnetic wave energy to the source of CMP slurry, applying a flow of the modified CMP slurry to a wafer polishing apparatus in which a substrate is positioned, and performing a polishing operation on the substrate.
[0008] In a first embodiment, a chemical mechanical planarization (CMP) method is provided, which includes the steps of: mixing (1) an aqueous CMP slurry, (2) an encapsulating agent forming a supramolecular structure selected from the group consisting of vesicles, micelles, polyelectrolytes, and liposomes, and (3) a material additive selected from the group consisting of ligands, ligand-metal complexes, and non-metal reactive-oxygen species (ROS) catalysts, thereby forming a modified slurry, providing at least one of mechanical wave energy or electromagnetic wave energy to the modified slurry, thereby forming an activated modified slurry, and planarizing the substrate while the substrate is exposed to the activated modified slurry.
[0009] In a second embodiment, a chemical mechanical planarization (CMP) method is provided, which includes the steps of: (1) mixing an aqueous CMP slurry; (2) an encapsulating agent forming a supramolecular structure selected from the group consisting of vesicles, micelles, polyelectrolytes, and liposomes; and (3) a material additive selected from the group consisting of ligands, ligand-metal complexes, and non-metal reactive oxygen species (ROS) catalysts, thereby forming a modified slurry, the material additive having a water solubility of less than 20 grams per liter when measured at 22° C.; providing mechanical wave energy to the modified slurry, thereby forming an activated modified slurry; and planarizing the substrate while the substrate is exposed to the activated modified slurry.
[0010] This brief description of the invention is intended only to provide a brief overview of the subject matter disclosed herein according to one or more exemplary embodiments, and is not intended to serve as a guide for interpreting the claims or for defining or limiting the scope of the invention, which is defined solely by the appended claims. This brief description is provided to introduce in a simplified form an exemplary selection of concepts that are further described below in the Detailed Description. This brief description is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used as an aid in determining the scope of the claimed subject matter. The claimed subject matter is not limited to implementations that solve any or all of the shortcomings noted in the Background. [Brief description of the drawings]
[0011] So that the features of the present invention may be understood, a detailed description of the present invention may be made by reference to certain embodiments, some of which are illustrated in the accompanying drawings. It should be noted, however, that the drawings illustrate only certain embodiments of the present invention and therefore should not be considered as limiting the scope of the present invention, as it encompasses other equally effective embodiments. The drawings are not necessarily to scale, and the emphasis is generally on illustrating the features of certain embodiments of the present invention. In the drawings, like numerals are used to indicate like parts throughout the various views. Accordingly, for a better understanding of the present invention, reference may be made to the following detailed description read in conjunction with the drawings. [Figure 1] FIG. 1 illustrates elements of a CMP slurry processing system, according to some embodiments. [Figure 2A] FIG. 1 is a flow diagram of a CMP method, according to some embodiments. [Figure 2B] FIG. 4 is a flow diagram of a CMP method according to another embodiment. [Figure 2C] FIG. 4 is a flow diagram of a CMP method according to another embodiment. [Figure 2D]FIG. 4 is a flow diagram of a CMP method according to another embodiment. [Figure 2E] FIG. 4 is a flow diagram of a CMP method according to another embodiment. [Diagram 3] FIG. 1 is a schematic diagram of a CMP slurry processing system, according to some embodiments. [Figure 4A] FIG. 1 illustrates a perspective view of a slurry processing system according to some embodiments. [Figure 4B] FIG. 4B is a top view of the slurry processing system of FIG. 4A. [Figure 4C] FIG. 4B is a top view of the slurry processing system of FIG. 4A with the cover seal system removed from the vessel housing revealing the interior of the vessel housing. [Diagram 5] FIG. 4B is a cross-sectional front view of the slurry processing system of FIG. 4A. [Figure 6A] FIG. 6 is an exploded view of the slurry processing system of FIGS. 4A and 5. [Figure 6B] FIG. 5 is a close-up cross-sectional front view of a sealing area of the slurry processing system of FIGS. 4A-6A. [Figure 7] 1 is a bar graph showing a comparison of material removal rates for different CMP processes including the use of a slurry. [Figure 8] FIG. 1 illustrates the operation of a slurry injection system in combination with a slurry processing system according to some embodiments. [Figure 9A] FIG. 1 is a flow diagram illustrating the operation of a light-generating system of a slurry processing system according to some embodiments. [Figure 9B] FIG. 11 is a flow diagram illustrating the operation of a light-generating system of a slurry processing system according to another embodiment. [Figure 9C] FIG. 4 is a flow diagram illustrating the operation of a slurry processing system according to another embodiment. [Figure 10] FIG. 1 is a flow diagram illustrating one method for planarizing a substrate. [Figure 11] 1 is a graph showing material removal rates for various test conditions. [Figure 12]1 is a graph showing the change in material removal rate as a function of water solubility of a ROS additive. [Figure 13A] 1 shows the chemical structures of various encapsulating agents capable of forming micelles. [Figure 13B] 1 shows the chemical structures of various encapsulating agents capable of forming micelles. [Figure 14] 1 shows the chemical structures of various encapsulating agents capable of forming vesicles. [Figure 15] 1 shows the chemical structures of various encapsulating agents that are polyelectrolytes. [Figure 16] 1 shows the chemical structures of various encapsulating agents capable of forming liposomes. [Figure 17] 1 shows the chemical structures of various material additives that form additional ROS under the disclosed conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In the following detailed description, numerous specific details are set forth by way of example in order to provide a thorough understanding of the relevant teachings. However, it will be apparent to those skilled in the art that the present teachings may be practiced without such details. In other instances, well-known methods, procedures, components and / or circuits have been described at a relatively high level, without detail, in order to avoid unnecessarily obscuring aspects of the present teachings.
[0013] FIG. 1 is a block diagram of a slurry processing system 10 for a CMP process, according to some embodiments. The slurry processing system 10 is configured and arranged to provide a source of slurry, either an original slurry source 17 (shown in FIG. 2A) stored in a slurry holding tank 114, or a modified slurry 17A (shown in FIG. 1) that is enhanced or modified by one or more material additives 131, simply referred to as additives, e.g., chemical additives. In some embodiments, the modified slurry 17A is, for example, delivered from the slurry holding tank 114 and received by a slurry distribution system 110, and then delivered to a wafer polishing system 102, where it is alternatively or additionally enhanced or modified by a mechanical and / or electromagnetic energy source. Here, the system 102 includes a polishing head 104 that rotates a substrate 20 (e.g., a wafer) on a polishing pad 103 of the system 102. The polishing pad 103 can be a concentrically grooved or XY grooved polyurethane-based pad, or can have another pad configuration or construction material. The CMP wafer or substrate polishing system 102 may include other well-known components, such as motors, such as servo motors and / or inverter motors, electronics, actuators, wafer carriers, robots and wafer handling components, temperature sensors, retaining rings, shear and normal force transducers, IR detectors, etc., which are not shown for the sake of brevity. In some embodiments, the wafer carrier provides an average pressure in the range of 0.6-8 PSI and rotates at 15-200 RPM, but is not limited thereto. The top layer of the substrate 20 to be polished may be formed from one or more materials, such as copper, tungsten, aluminum, polysilicon, silicon dioxide, carbon-doped silicon dioxide, black diamond, silicon nitride, tantalum, tantalum nitride, titanium, titanium nitride, cobalt, gallium nitride, ruthenium, silicon carbide, or combinations or alloys thereof, used, for example, in shallow trench isolation (STI) CMP applications, which require the use of a slurry that can chemically react with the material(s) forming the substrate 20.In some embodiments, the substrate 20 has a wafer size of, but is not limited to, 200 mm or 300 mm. The original slurry source 17 or the modified slurry source 17A is delivered to the polishing pad 103 by a slurry distribution system 110. As mentioned above, the slurry 17 shown on the polishing pad 103 can be a ready-made or pure slurry source 17, or in other embodiments, it can be modified with material additives 131, referred to as modified slurry 17A.
[0014] In some embodiments, the slurry distribution system 110 includes one or more slurry holding vessels 114 , one or more additive holding devices 116 , and a wave energy source 133 .
[0015] The slurry holding vessel(s) 114 and / or additive holding device(s) 116 can be storage tanks, as well as other chemical additive delivery mechanisms, baffles, level sensors, chemical sensors, pumps, agitators, filters, on-board computers and controllers, flow meters, and the like. In some embodiments, the slurry holding vessel 114 can be a 20 liter tank including mixers, pumps, and sensors as described herein. These elements of the slurry distribution system 110 can control the quality of the source of slurry 17, for example, by agitating, mixing, filtering, circulating, or otherwise distributing the slurry 17. In some embodiments, the slurry distribution system 110 provides a flow rate in the range of 10-500 cc / min, but is not limited thereto, as illustrated by the embodiments herein.
[0016] In some embodiments, the wave energy source 133 includes an acoustic wave generating mechanism having one or more transducers or the like (not shown) that generate mechanical waves (e.g., sonic, cavitation, vibration, etc.) to acoustically activate the slurry liquid in the storage area of the slurry distribution system 110. In some embodiments, the acoustic wave generating mechanism can provide megasonic, ultrasonic, or related acoustic frequency spectrum acoustic energy. Application of the slurry to the substrate surface allows the passivation layer on the substrate surface (which is being polished continuously) to become softer and less dense by chemical reaction with the slurry, which reaction can be enhanced by sonication of the slurry. In doing so, depending on the sonication energy applied to the slurry during the sonication process prior to dispensing the slurry on pad 103, material removal rates (RR) and / or other removal characteristics for films made of copper, tungsten, polysilicon, aluminum, silicon dioxide, carbon-doped silicon dioxide, black diamond, silicon nitride, tantalum, tantalum nitride, titanium, titanium nitride, cobalt, gallium nitride, ruthenium, silicon carbide, or combinations or alloys thereof, are higher compared to without sonication. Furthermore, the softened aforementioned passivation layer formed by the electromagnetic wave activated chemical reaction with the sonicated slurry may result in lower wafer level defects and better polished surface quality for films made of copper, tungsten, polysilicon, silicon dioxide, aluminum, carbon-doped silicon dioxide, black diamond, silicon nitride, tantalum, tantalum nitride, titanium, titanium nitride, cobalt, gallium nitride, ruthenium, silicon carbide, or combinations or alloys thereof. A higher material removal rate is preferred because removal rate is inversely proportional to polishing time. Therefore, shorter production times increase the productivity of CMP modules in integrated circuit fabrication factories because wafer throughput increases. The resulting shorter polishing time also means that less slurry is needed to polish the wafers through the CMP process.This provides a cost advantage since slurry is the most expensive consumable in the CMP module. Furthermore, slurry can be hazardous to the environment and is also expensive to handle and legally dispose of, so it is a good step towards environmentally friendly manufacturing. Furthermore, it is preferable to achieve lower wafer level defects since excessive defects reduce product yield. Therefore, any reduction in defect levels and the quality of the surface finish of the polished material will improve productivity.
[0017] In some embodiments, the wave energy source 133 of the CMP slurry processing system 10 includes a source of electromagnetic waves (e.g., a light wave energy source) constructed and arranged to irradiate a source of slurry 17, for example, as shown in Figures 9A-9C. In some embodiments, the modified slurry 17A includes a material additive to induce ligand-to-metal-charge-transfer (LMCT) upon irradiation by the light wave energy source 112 (see Figures 9A-9C) of the wave energy source 133 to generate a photoactive slurry for the CMP operation. For example, by modulating the wavelength or intensity of the electromagnetic radiation by the light wave energy source 112, the removal rate and other process performance parameters can be modulated at the wafer level. The wavelength of the light can be in the range of 200-800 nm, but is not limited thereto. In some embodiments, the light wave energy source of the wave energy source 133 (shown in Figure 1) is in close proximity to the polishing pad 103 to irradiate the slurry prior to dispensing thereon. In these same embodiments, the acoustic source of the wave energy supply 133 (not shown in FIG. 1) is integrated with or is part of the slurry distribution system, for example as shown in FIGS. 3-6A.
[0018] The slurry processing system 10 may include a data analysis and reporting computer 12 that communicates with the wafer polishing system 102 and the slurry distribution system 110 via a dedicated processor 120. The processor 120 may communicate with a controller 122 to manage and control the operation of the polisher and the injector.
[0019] 2A is a flow diagram of a CMP method, according to some embodiments, in which the method 200 may include some or all of the elements of the CMP slurry processing system 10 of FIG.
[0020] Method 200 may begin at step 202, where a source of slurry 17 is modified to form a modified slurry 17A that includes one or more material additives 131, e.g., chemical additives. In other embodiments, the slurry is unmodified, e.g., a pre-made slurry or other commercially available slurry 17. The material additives 131 may be selected based on their function, e.g., as described in the examples below. In other embodiments, other slurry additives may modify the liquid surface tension and contact angle with the substrate, e.g., as described in the examples below.
[0021] In step 204, a source of mechanical energy, e.g., sonic energy, and / or electromagnetic energy, e.g., light wave energy, is applied to the modified slurry 17A. In some embodiments, the method 200 does not include step 202 and proceeds directly to step 204, in which case the ready-made or unmodified slurry 17 does not include additives 131. In some embodiments, the slurry can flow through a megasonication and / or light enhancement process performed by a wave energy source 133 in step 206 before dispensing onto the polishing pad 103, such as as part of a CMP process. In some embodiments, a light-activated rate-enhancing material is added to the slurry, which can increase the material removal rate when the slurry is excited with a light wave energy source of the wave energy source 133. In some embodiments, an additive including a light-activated composite vehicle is applied in addition to or instead of the material additive of step 202. In some embodiments, the wave energy source 133 may operate in conjunction with a slurry injection system, for example, as illustrated in Figure 8 and / or described in one or more of U.S. Patent No. 8,197,306, U.S. Patent No. 8,845,395, U.S. Patent No. 9,296,088, Korean Patent No. 1,394,745, Japanese Patent No. 5,574,597, and Taiwanese Patent No. 1,486,233, each of which is incorporated above by reference in its entirety.
[0022] 2B is a flow diagram of a CMP method 210 according to another embodiment. In step 212, the source of slurry 17 is unmodified before being received by a wave energy source 133, which applies a source of mechanical wave energy (e.g., sonic wave energy) and / or electromagnetic wave energy (e.g., light wave energy) to the unmodified slurry 17 (step 214).
[0023] In step 215, the supply of slurry in the wave energy source 133 is further modified with one or more chemical additives 131, which are provided to the wave energy source separately from the pre-made or commercially available slurry. In this embodiment, the wave energy source 133 includes a device for applying electromagnetic (e.g., light wave) energy, as well as a holding device or area for receiving, temporarily holding, and applying the material additive(s) 131 to the slurry in the wave energy source 133. In some embodiments, step 214 is performed before step 215. In other embodiments, steps 214 and 215 are performed simultaneously. In other embodiments, step 214 is performed after step 215.
[0024] In step 216, a polishing operation is performed with the slurry modified by both the material additive(s) 131 and the wave energy source 133.
[0025] 2C is a flow diagram of a CMP method 220 according to another embodiment. Step 222 may be similar to step 202 of FIG 2A, in which a source of slurry 17A is modified to include one or more material additives 131. In step 223, the modified slurry 17A is delivered to the polishing system 102.
[0026] In step 224, a megasonication and / or light enhancement process is applied to the polishing pad 103 of the polishing system 102 on which the modified slurry 17A of step 223 is provided.
[0027] In step 226, a polishing operation is performed on the slurry that has been modified by both the material additives of step 222 and the megasonication and / or light-enhanced process of step 224.
[0028] 2D is a flow diagram of a CMP method 230 according to another embodiment. Unmodified slurry 17 and material additive 131 are separately delivered to polishing system 102 (steps 232 and 233, respectively). In step 234, a megasonication and / or light enhancement process is brought to polishing pad 103 on which slurry 17 of step 232 and material additive 131 of step 233 are separately provided.
[0029] In step 236, a polishing operation is performed on the slurry 17 modified by the material additives 131 in step 233 and by the energy source 133 that applies the megasonication and / or light enhancement process in step 234, which are independently provided to the polishing system 102.
[0030] 2E is a flow diagram of a CMP method 240 according to another embodiment. In step 242, a source 17 of pre-made or commercially available slurry is provided to the polishing system 102. In step 243, the material additive 131 is provided to a wave energy source 133, which applies mechanical wave energy and / or electromagnetic wave energy to the material additive 131. In step 244, a megasonication and / or light-enhanced process provides modified additive 131 on the polishing pad 103 on which the slurry 17 of step 242 is separately provided.
[0031] At step 246, in response to receiving and processing the additive 131 modified by the wave energy source 133 at step 244, a grinding operation is performed on the previously unmodified slurry 17 in the grinding system 102 to form modified slurry 17A.
[0032] 3 is a schematic diagram of a CMP slurry processing system 300, according to some embodiments. The slurry processing system 300 may be part of the distribution system 110 of FIG. 1. The slurry processing system 300 is constructed and arranged to energize, agitate, mix, filter, circulate, and / or distribute a supply of slurry to a substrate surface. Some of these well-known slurry distribution features will not be described in detail for the sake of brevity. Other features will be described in more detail as they include applications, modifications, and variations that fall within the true scope of the inventive concept.
[0033] In some embodiments, the CMP slurry processing system 300 includes a storage container housing 302, an ultrasonic agitation device 304, piping 306 having a non-coiled inlet region 311, a non-coiled outlet region 321, and a coiled portion 313 between the non-coiled inlet region 311 and the non-coiled outlet region 321, and a generator 308.
[0034] The vessel housing 302 is constructed and arranged as an open-topped bowl or the like for receiving and holding a source of deionized water 320 positioned about the tubing 306. In some embodiments, the top of the housing 302 is sealed and includes an inlet for receiving the deionized water 320. The deionized water 320 can fill the vessel housing 302 to a level 322 such that the coiled portion 313 of the tubing 306 is submerged in the water and the non-coiled inlet region 311 extends away from the vessel housing 302 holding the deionized water 320. The tubing 306 can receive a source of liquid, such as a slurry, that flows from an inlet at the non-coiled inlet region 311 to an outlet at the non-coiled outlet region 321 for distribution onto a CMP polisher. As the slurry liquid passes through the coiled section 313 of the tubing 306 submerged in water, the generator 308 activates the sonic agitation device 304 to sonically agitate or excite the water with sufficient energy to propagate sonic waves through the plastic surface of the tubing 306 and into the slurry liquid as the slurry flows through the coiled section 313 to the non-coiled exit region 321 of the tubing 306 and then to a pad on the platen of a CMP polisher, for example, as shown in FIG. 1. In some embodiments, the sonic agitation device 304 includes one or more sonic transducers. In some embodiments, the generator 308 is an integrated RF generator.
[0035] 4A-6B show a slurry processing apparatus 400 according to some embodiments. The slurry processing apparatus 400 may be a part of the slurry processing system 10 of FIG. 1 or may be entirely composed of the slurry processing system 10. However, the slurry processing system 10 of FIG. 1 is not limited to the slurry processing apparatus 400. For example, the slurry processing system 300 of FIG. 3 may be incorporated as a part of the slurry processing system 10 of FIG. 1. The difference between the slurry processing apparatus 400 and the CMP slurry processing system 300 of FIG. 3 is that the slurry processing apparatus 400 of FIG. 4A-6A is sealed and leak-proof, allowing the apparatus 400 to provide a continuous and direct flow of any type of CMP slurry. In addition, the slurry processing apparatus 400 can process slurries without coiled piping. The slurry processing apparatus 400 is constructed and arranged to reduce inefficiencies that may occur in ultrasonic processing of CMP slurries for polishing operations where the slurry may receive 5% or less of the acoustic energy.
[0036] In some embodiments, slurry processing apparatus 400 includes a vessel housing 402, a cover seal system 410, and a set of inlets, outlets, and connectors 411-413, 418, and 421.
[0037] The vessel housing 402 is constructed and arranged to be hermetically sealed by a cover seal system 410 (shown in detail in FIG. 6B). The vessel housing 402 is constructed and arranged to receive and hold a source of slurry, and further to allow a continuous flow of the slurry from an outlet 412. As shown in FIG. 4C, an opening 403 exposes an interior 408 of the housing 402. In some embodiments, the interior 408 is formed of Teflon™ or the like. The interior 408 can include an active area within the interior 408, in which an acoustic resonator or other acoustic energy generating device 431 is enclosed within a transducer housing 430 (see FIG. 5) and sealed within the vessel housing 402, and can provide acoustic energy to a source of slurry, either modified slurry 17A modified with chemical additives or unmodified slurry 17. In some embodiments, the acoustic energy generating device may be a light wave energy source similar to or the same as a light wave energy source, which may be, for example, external to the vessel housing 402 and provides light to the source of the slurry flowing from the outlet tube 412, or may be in the interior 408 of the vessel housing 402. In some embodiments, the light wave energy source is separate from the acoustic energy generating device of the vessel housing 402. In some embodiments, the acoustic energy generating device may be part of, similar to, or the same as the wave energy source 133 of Figures 1-2E, or the sonic agitation device 304 of Figure 3, and therefore details thereof have been omitted for the sake of brevity. A power source (not shown in Figures 4A-6A, but which may be similar to the generator 308 of Figure 3) may provide power to the acoustic energy generating apparatus. The power source may be similar to or the same as the generator 308 of Figure 3, and therefore details thereof have been omitted for the sake of brevity.In some embodiments, the acoustic energy generating device applies a piezoelectric effect to generate sound waves and cavitation that agitate the slurry, which is then directed to a polishing pad on top of a platen of the polishing system 102 (see FIG. 1 ), where it polishes the surface of the substrate 20 by removing it by forming a chemical passivation layer on the surface of the substrate, which is then mechanically polished by the pad and carried away by the slurry.
[0038] 4A, 6A, and 6B, the cover seal system 410 is constructed to form a fluid-tight seal over the opening 403 of the vessel housing 402. The vessel housing 402 may be constructed, e.g., machined, to fit or mate with the clamp portions 401A, 401B and the cover element 409 to maintain a sealed compression interface between the cover seal system 410 and the vessel housing 402. In some embodiments, the cover seal system 410 includes a slip fit element 401, a recessed capture O-ring 404, a shear ring 405, and a cover element 409. Details of the cover seal system 410 are described below.
[0039] In some embodiments, the slurry processing apparatus 400 includes an inlet tube 411, an outlet tube 412, a vent tube 413 (each also referred to as a line), and a gas inlet tube 418 that are mounted on and extend through a circular disk, such as an O-ring 404. In some embodiments, the outlet tube 412 has a length that is longer than the lengths of the inlet tube 411 and the vent tube 413, such that a portion of the outlet tube 412 extends through at least a portion of the interior of the vessel housing 402 and is submerged in the slurry within the vessel housing. The inlet tube 411 and the vent tube 413 may extend from a hole in the O-ring 404 in a direction away from the vessel housing 402. In some embodiments, the three tubes 411-413 are press-fitted and have heights that can be individually adjusted by loosening a nut 415 (see FIG. 4B) that holds the tubes in place. When nut 415 is loosened, the tube is free to move up and down to a desired height from the surface of cover element 409. The nut can then be tightened to secure the tube against cover element 409, the tube is moved up or down to a desired height, and then the nut is tightened so that the tube is held securely. Tubes 411-413 and 418 may be compression fitted and may be replaceable.
[0040] Inlet pipe 411 provides a slurry inlet to the closed system. Vent pipe 413 provides a vent line 30 that allows trapped air to escape from housing 402 during an initial priming operation where the vessel receives and becomes somewhat or partially filled with slurry before a valve 414 on vent pipe 413 is closed, allowing housing 402 to receive a continuous slurry flow from inlet 411 through cover seal system 410 which provides a fluid tight seal at opening 403.
[0041] Gas inlet tube 418 is configured to inject or permeate a gas, such as ozone or oxygen, into vessel housing 402 .
[0042] In some embodiments, the connectors 421 at the bottom of the housing 402 shown in FIG. 4A can include, but are not limited to, a purge gas return, an RF cable inlet, and a temperature sensor cable, respectively.
[0043] 6A and 6B, in some embodiments, the vessel housing 402 has a groove 407 machined or otherwise formed about the housing 402 proximate the vessel opening 403 for receiving and fitting the shear ring 405 in place such that the shear ring 405 can provide a fluid-tight seal about the vessel housing 402 when the cover element 409 is removably attached about the vessel opening 403. The shear ring can be made of, for example, DELRIN®.
[0044] The O-ring 404 may be formed from a material (e.g., rubber, plastic, etc.) that allows the retaining O-ring 404 to provide a fluid-tight seal. Specifically, the O-ring 404 seals an upper region of the vessel housing 402 similarly or similarly to the inner diameter of the interior 408 of the vessel housing 402, limited only by the tolerances of the vessel housing 402. In some embodiments, the upper sealing surface and the groove under the cover element 409 in which the O-ring 404 is positioned may be machined for a smooth finish. When the O-ring 404 is installed, the O-ring 404 maintains a sealed compression interface between the cover seal system 410 and the vessel housing 402. In some embodiments, the O-ring 404 is formed from Solid Virgin TEFLON®™. In some embodiments, the O-ring 404 is formed from a fluoroelastomer material such as VITON™ to form a FEP sealed VITON™ O-ring, which provides sufficient compression with a high degree of chemical resistance.
[0045] The cover element 409, also referred to as a lid, may be disk-shaped and may have a threaded peripheral region 422. The mating element 401, also referred to as a clamp, includes a first clamp portion 401A and a second clamp portion 401B, which are constructed and arranged to couple to each other. In doing so, the first clamp portion 401A includes two rods 423, also referred to as threaded rods, extending from a body of the first clamp portion 401A. In some embodiments, the body has a hemispherical interior 424. The rods 423 are insertable into a hole in the second clamp portion 401B, which also has a hemispherical interior 424 (see FIG. 6B). When coupled to each other, the first clamp portion 401A and the second clamp portion 401B collectively have a central hole formed by the hemispherical interior 424, which is also threaded to mate with the peripheral region 422 of the cover element 409. The rod 423 also prevents torque or other rotational forces from occurring that may separate the clamping portions 401A, 401B from one another or otherwise affect the seal formed between the cover seal system 410 and the container housing 402. The hemispherical interior 424 includes a threaded collar that surrounds the threaded peripheral region 422 and forms a threaded relationship. In some embodiments, the peripheral region 422 is constructed and arranged to taper or have an angle with respect to the threaded interior of the hemispherical interior 424, for example, as shown. For example, the angle may be 45 degrees from a vertical axis such that the bottom surface of the disk has a width, circumference, diameter, or related dimension that is greater than the width, circumference, diameter, or related dimension of the top surface. The rod 423 or pin, or the like, may be threaded to form a threaded relationship with a wing nut 406 that, when rotated, may tighten the first clamping portion 401A and the second clamping portion 401B against one another. Wing nut 406 is hand tightened for easy removal and assembly and is designed to allow users of all sizes and sizes to handle it using gloves.The wing nut 406 terminates in a clamp formed by the first clamp portion 401A and the second clamp portion 401B of the slipping element 401 at exactly the correct distance for compression of the O-ring 404 and / or the shear ring 405. The threaded collar of the slipping element 401, the rod 423, and the wing nut 406 can collectively form a string seal that surrounds the cover element 409 and forms a string seal in the cover seal system 410. The cover seal system 410, particularly the O-ring 404, then forms a seal with the shear ring 405 and the vessel housing groove 407. In some embodiments, the O-ring 404 and the shear ring 405 form a "clamshell" arrangement for sealing the opening 403 of the vessel housing 402. Another feature is that the slurry processing apparatus 400 can be operated by one person. Clamping portions 401A, 401B may be replaceable since each can independently rest on O-ring 404 or otherwise apply force to the O-ring, and can be added to or removed from container housing 402 one at a time. Wing nut 406 and rod 423 may be replaceable and can be removed one at a time since each can reside separately within a groove in clamping portions 401A, 401B.
[0046] During the CMP polishing process, slurry liquid is injected into the interior 408 of the housing 402 through inlet 411 and exits the housing 402 through outlet 412. Polishing results obtained using various methods are shown in FIG. 7. Specifically, removal rate results from a copper CMP operation using bulk copper slurry or the like are obtained with no sonication performed (methods 1 and 4), tube sonication (methods 2 and 5, shown in FIG. 3), and continuous flow sonication (methods 3 and 6, shown in FIGS. 4A-6A). A significant increase in material removal rate is shown with methods 3 and 6 performed by the slurry processing apparatus 400 of FIGS. 4A-6A. More specifically, the bar graph in FIG. 7 shows a higher copper removal rate at an operating wafer pressure of 1 PSI as the removal rate increases. At 3 PSI, even more favorable copper removal rate results are achieved using the slurry processing apparatus 400.
[0047] Figure 8 is a diagram illustrating the operation of a slurry injection system 800 in combination with a slurry processing apparatus 400, according to some embodiments. Although the slurry processing apparatus 400 of Figures 4A-6A is shown, the slurry processing system 10 of Figure 1 is equally applicable. For example, the slurry injection system 800 can be part of the slurry processing system 10 along with the slurry processing apparatus 400.
[0048] The slurry injection system 800 is constructed and arranged to couple to a rotary substrate polisher on which a substrate 20 is positioned, such as the wafer polishing system 102 of Figure 1. During a polishing operation, the slurry injection system 800 is positioned relative to the substrate 20 rotating on the pad 103 of the polisher such that a supply 17A of modified slurry is dispensed along a track that includes holes in the bottom of the injection system.
[0049] In some embodiments, the slurry is modified by wave energy source 133 and delivered from wave energy source 133 to slurry injection system 800. Slurry injection system 800 can then deliver the slurry to polishing pad 103 via holes and / or tracks.
[0050] 9A-9C illustrate various applications of the light wave energy source 112 of the wave energy source 133 of the CMP slurry processing system, according to some embodiments. The light wave energy source 112 may include a pump or the like that can provide a source of slurry to one or more light emitting elements, and then provide the slurry from the light wave energy source 112 that has been modified by the light energy emitted by the light emitting elements.
[0051] The method 900 shown in FIG. 9A may begin at step 902, where a source of slurry 17 is modified to form a modified slurry 17A that includes one or more material additives 131, e.g., chemical additives. In other embodiments, the slurry is unmodified, e.g., a pre-made slurry or other commercially available slurry 17. The material additives 131 may be selected based on their function, e.g., as described in the examples below. In other embodiments, other slurry additives may modify the liquid surface tension and contact angle with the substrate, e.g., as described in the examples below.
[0052] In step 904, the lightwave energy source 112 applies electromagnetic energy, e.g., light, to the modified slurry 17A. In some embodiments, the lightwave energy source 112 is integrated into the slurry processing system, e.g., part of the wave energy source 133 of the slurry processing system 10 of FIG. 1, or integrated into the vessel housing 402 of the slurry processing apparatus 400 of FIGS. 4A-6A. In other embodiments, the lightwave energy source 112 is separate from the slurry processing system, e.g., in close proximity to the substrate 20 on the polishing pad 103 shown in FIG. 1. In some embodiments, the lightwave energy source acts on a light-activated rate-enhancing material additive in the slurry. In some embodiments, an additive comprising a light-activated composite vehicle is applied in addition to or instead of the material additive of step 902. In some embodiments, the lightwave energy source may operate in conjunction with a slurry injection system, such as that illustrated in Figure 8 and / or described in one or more of U.S. Patent No. 8,197,306, U.S. Patent No. 8,845,395, U.S. Patent No. 9,296,088, Korean Patent No. 1,394,745, Japanese Patent No. 5,574,597, and Taiwanese Patent No. 1,486,233, each of which is incorporated above in its entirety.
[0053] In step 906, a polishing operation is performed on the slurry modified by both the material additive(s) 131 and the light wave energy source 112.
[0054] The method 910 shown in FIG. 9B includes steps 912 and 914 that are similar to steps 902 and 904 of FIG. 9A and therefore will not be repeated for the sake of brevity.
[0055] In step 916, the slurry, modified by both the material additive(s) 131 and the light wave energy source 112, is directed to the sonic energy source 113. In some embodiments, the slurry may flow through a mega-sonication process performed by the wave energy source 133. In some embodiments, the sonic energy source 113 is integrated into the slurry processing system, e.g., part of the wave energy source 133 of the slurry processing system 10 of FIG. 1, or integrated into the vessel housing 402 of the slurry processing apparatus 400 of FIGS. 4A-6A. In other embodiments, the sonic energy source 113 is separate from the slurry processing system, e.g., in close proximity to the wafer 20 on the polishing pad 103 shown in FIG. 1.
[0056] In step 918, a polishing operation is performed on the slurry modified by each of the material additive(s) 131, the light wave energy source 112, and the sonic energy source 113.
[0057] Method 920 shown in Figure 9C includes steps 922 and 924 similar to steps 902 and 904 of Figure 9A and steps 912 and 914 of Figure 9B, and therefore will not be repeated for brevity. Method steps 920 are similar to method 910 of Figure 9B, except that the slurry modified with each of the material additive(s) 131 is first presented to sonic energy source 113 in step 926 and then to polishing system 102 in step 928.
[0058] In FIG. 10, a method 1000 is shown. The method 1000 includes a step 1002 of mixing (1) an aqueous CMP slurry, (2) an encapsulating agent that forms a supramolecular structure, and (3) a material additive that generates additional reactive oxygen species (ROS) under disclosed conditions. Under reaction conditions, the encapsulating agent forms a supramolecular structure selected from the group consisting of vesicles, micelles, polyelectrolytes, and liposomes. Without wishing to be bound by any particular theory, the supramolecular structure liberates the material additive, which then generates additional ROS, when exposed to mechanical or electromagnetic energy. The supramolecular structure and material additive effectively function as a polymeric Fenton additive (MFA), allowing additional or alternative reactive oxygen species that would not normally be available (or would perform poorly) to be utilized in the method 1000. For example, the supramolecular structure may allow a material additive with low aqueous solubility to be utilized. Such compounds are liberated when the supramolecular structure is exposed to mechanical or electromagnetic energy. In step 1004, wave energy (e.g., mechanical wave energy and / or electromagnetic wave energy) is supplied directly to the modified slurry, thereby forming an activated modified slurry. The wave energy is believed to disrupt the supramolecular structure and release the material additives to form additional reactive oxygen species.
[0059] In one embodiment, the wave energy is 0 Watts / cm 2 Ultra-low power of 2 watts / cm 2 In another embodiment, the sonication is at 0.5 Watts / cm 2 Not less than 1.5 watts / cm 2 In step 1006, the substrate is planarized while exposed to the activated modified slurry.
[0060] Without wishing to be bound by any particular theory, it is believed that application of the modified slurry to the substrate allows the passivation layer on the substrate surface to become softer and less dense. This enhances the polishing process in several ways. The disclosed method allows polishing to be performed at an acceptable material removal rate while using lower applied pressure and / or gentler conditions. This reduces defects that may occur during polishing. Additionally, faster material removal rates can also be achieved.
[0061] Step 1002 of method 1002 can be performed in a variety of ways. In one embodiment, the encapsulating agent and the material additive are added separately to the CMP slurry. Alternatively, the encapsulating agent and the material additive may be premixed in water to form a composition. This composition is then added to the CMP slurry. For example, an aqueous solution may be formed that is 10% (m / v) encapsulating agent and 1% (m / v) material additive in water. In this exemplary composition, the material additive is present in an amount of 10% by weight relative to the weight of the encapsulating agent.
[0062] In some premixed embodiments, the mixed solution may be incubated at room temperature without direct wave agitation for a period of time. Without wishing to be bound by any particular theory, it is believed that this incubation provides time for the encapsulating agent to encapsulate the material additive. For example, a premixed solution prepared using a 5 minute incubation time showed a dramatic improvement in material removal rate (from about 4,100 Å / min to about 8,500 Å / min) compared to a premixed solution prepared using a 1 minute incubation time. In one embodiment, the premixed solution is allowed to incubate for a period of more than 2 minutes but less than 10 minutes. In another embodiment, the premixed solution is allowed to incubate for at least 5 minutes.
[0063] The material additive is generally present in an amount between 1.0% (m / m) and 100% (m / m) by weight of the encapsulating agent. In one embodiment, the material additive is present in an amount between 1% (m / m) and 50% (m / m) by weight of the encapsulating agent. In another embodiment, the material additive is present in an amount between 1% (m / m) and 20% (m / m) by weight of the encapsulating agent. In yet another embodiment, the material additive is present in an amount between 5% (m / m) and 15% (m / m) by weight of the encapsulating agent.
[0064] Sufficient amounts of the encapsulating agent and the material additive are used such that, after mixing with the CMP slurry, the overall solution is between 0.01% (m / v) and 10.0% (m / v) of the encapsulating agent and the material additive, based on the total volume of the solution. In one embodiment, the concentration is between 0.01% (m / v) and 5.0% (m / v), based on the total volume of the solution. In another embodiment, the concentration is between 0.05% (m / v) and 2.5% (m / v), based on the total volume of the solution. In yet another embodiment, the concentration is between 0.05% (m / v) and 2% (m / v), based on the total volume of the solution.
[0065] By way of illustration and not by way of limitation, Figure 11 shows several examples of the method 1000. Each test shows the performance of a commercial bulk copper slurry mixed with water and hydrogen peroxide (per manufacturer's specifications). In the following tests, all percentages are mass / volume percentages.
[0066] Test 1: No encapsulant, no material additives, no sonication, control: This test was performed using a commercial bulk copper slurry (CoppeReady3930® from Versum Materials). The copper metal substrate was polished for 1 minute with a down force of 3 PSI and a platen speed of 100 RPM. The slurry flow rate was maintained constant at 65 mL / min.
[0067] Test 2: Sonication was performed without encapsulant or material additives, Control: This test was performed using a commercial bulk copper slurry (CoppeReady 3930® from Versum Materials). The copper metal substrate was polished for 1 minute with a down force of 3 PSI and a platen speed of 100 RPM. The slurry flow rate was maintained constant at 65 mL / min. The slurry was sonicated in a continuous flow sonicator at 1.0 Watts / cm. 2 The modified slurry was incubated for 5 minutes prior to polishing testing. Sonication resulted in a +12% increase in material removal rate (Å / min) compared to Test 1.
[0068] Tests 3 and 4 utilize method 1000 with and without sonication. Tests 3 and 4 specifically utilize poloxamer as the encapsulating agent and salicylhydroxamic acid (SHA) as the material additive.
[0069] Test 3: Poloxamer as the encapsulant, SHA as the material additive, no sonication: This test was performed using a commercial bulk copper slurry (CoppeReady 3930® from Versum Materials). The solution was premixed and contained 10% P-103 (a commercial poloxamer), 1% salicylhydroxamic acid (SHA), and water. The solution was added to the slurry at 0.1%. A copper metal substrate was polished for 1 minute with a down force of 3 PSI and a platen speed of 100 RPM. The slurry flow rate was maintained constant at 65 mL / min.
[0070] Test 4 - Sonication using poloxamer as the encapsulant and SHA as the material additive: This test was performed using a commercial bulk copper slurry (CoppeReady 3930® from Versum Materials). The solution was premixed and contained 10% P-103 (a commercial poloxamer), 1% salicylhydroxamic acid (SHA), and water. The solution was added to the slurry at 0.1%. A copper metal substrate was polished for 1 minute with a down force of 3 PSI and a platen speed of 100 RPM. The slurry flow rate was maintained constant at 65 mL / min. The resulting slurry was sonicated in a continuous flow sonicator at 1.0 watts / cm. 2 The slurry was sonicated at 100 rpm for 5 min. Prior to polishing testing, the slurry was incubated for 5 min. Sonication resulted in a dramatic +32% increase in material removal rate (Å / min) compared to Test 3.
[0071] Tests 5 and 6 utilize method 1000 with and without sonication. Tests 5 and 6 specifically utilize poloxamer as the encapsulating agent and tryptophan (TRYP) as the material additive.
[0072] Test 5: Poloxamer as the encapsulant, TRYP as the material additive, no sonication. This test was performed using a commercial bulk copper slurry (CoppeReady3930® from Versum Materials). The solution was premixed and contained 10% P-103 (a commercial poloxamer), 1% tryptophan, and water. The solution was added to the slurry at 0.1%. A copper metal substrate was polished for 1 minute with a down force of 3 PSI and a platen speed of 100 RPM. The slurry flow rate was maintained constant at 65 mL / min.
[0073] Test 6: Sonication with Poloxamer as the encapsulant and TRYP as the material additive: This test was performed with a commercial bulk copper slurry (CoppeReady 3930® from Versum Materials). The solution was premixed and contained 10% P-103 (a commercial poloxamer), 1% tryptophan, and water. The solution was added to the slurry at 0.1%. A copper metal substrate was polished for 1 minute with a down force of 3 PSI and a platen speed of 100 RPM. The slurry flow rate was maintained constant at 65 mL / min. The resulting slurry was sonicated in a continuous flow sonicator at 1.0 watts / cm. 2 The slurry was sonicated at 100 rpm for 5 min. Prior to polishing testing, the slurry was incubated for 5 min. Sonication resulted in a +18% increase in material removal rate (Å / min) compared to Test 5.
[0074] Tests 7 and 8 utilize method 1000 with and without sonication. Tests 7 and 8 specifically utilize poloxamer as the encapsulating agent and phenylalanine (PA) as the material additive.
[0075] Test 7: Poloxamer as the encapsulant, PA as the material additive, no sonication: This test was performed using a commercial bulk copper slurry (CoppeReady 3930® from Versum Materials). The solution was premixed and contained 10% P-103 (a commercial poloxamer), 1% phenylalanine, and water. The solution was added to the slurry at 0.1%. A copper metal substrate was polished for 1 minute with a down force of 3 PSI and a platen speed of 100 RPM. The slurry flow rate was maintained constant at 65 mL / min.
[0076] Test 8: Sonication with Poloxamer as the encapsulant and PA as the material additive: This test was performed with a commercial bulk copper slurry (CoppeReady 3930® from Versum Materials). The solution was premixed and contained 10% P-103 (a commercial poloxamer), 1% phenylalanine, and water. The solution was added to the slurry at 0.1%. A copper metal substrate was polished for 1 minute with a down force of 3 PSI and a platen speed of 100 RPM. The slurry flow rate was maintained constant at 65 mL / min. The resulting slurry was sonicated in a continuous flow sonicator at 1.0 Watts / cm. 2 The slurry was sonicated at 100 rpm for 5 min. Prior to polishing testing, the slurry was incubated for 5 min. Sonication resulted in a +13% increase in material removal rate (Å / min) compared to Test 7.
[0077] [Table 1]
[0078] FIG. 12 is a graph of the change in material removal rate by ultrasonication as a function of additive solubility. Without wishing to be bound by any particular theory, it is believed that the dramatic +32% enhancement is due to the low solubility of salicylhydroxamic acid (SHA). The disclosed method allows for the use of material additives, such as SHA, that have low water solubility. In one embodiment, a material additive is used that has a water solubility of less than 20 grams per liter, as measured at 22° C. in deionized water. In another embodiment, a material additive is used that has a water solubility of less than 10 grams per liter, as measured at 22° C. in deionized water.
[0079] The encapsulating agent forms a supramolecular structure selected from the group consisting of vesicles, micelles, polyelectrolytes, and liposomes.
[0080] 13A and 13B show examples of encapsulating agents that form micelles. Micelles are monolayer aggregates of molecules that have both polar and non-polar regions. Poloxamers (polymerization products of ethylene oxide and propylene oxide) may be used. A number of poloxamers are known with different molecular weight ranges of propylene oxide (PO) chains and weight percentages of ethylene oxide (EO) chains. The molecular weight range of the PO chains is generally in the range of 950 Daltons to 4000 Daltons. The weight percentage of the EO chains typically ranges from 10% to 80%. Examples of commercially available poloxamers are shown in Table 2.
[0081] [Table 2]
[0082] Further examples of encapsulating agents that form micelles include cationic micelles and anionic micelles. Cationic micelles include, but are not limited to, organic quaternary ammonium salts. Examples of organic quaternary ammonium salts include hydrogen trialkano ammonium salts (e.g., triethylamine hydrochloride, cetrimonium bromide, benzethonium chloride, dimethyldioctadecyl ammonium chloride, ANDOGEN®, cetylpyridinium chloride, and octenidine dihydrochloride). Anionic micelles include sulfate ester salts and carboxylate salts having at least 10 carbons. Examples of sulfate ester salts include sodium laureth sulfate and sodium lauryl sulfate. Examples of carboxylate salts include stearates, lauroyl sarcosines, glycolic acid ethoxylate 4-tert-butylphenyl ether salts, zonyl fluorosurfactant salts, cholates, deoxycholates, glycolic acid ethoxylate lauryl phenyl ether, and glycolic acid ethoxylate oleyl ether salts.
[0083] FIG. 14 shows examples of encapsulating agents that form vesicles. Vesicles are bilayer aggregates of molecules that have both polar and non-polar regions. Examples of vesicles include sorbitan esters, such as sorbitan esters and polyethylene glycol sorbitan esters. Examples of polyethylene glycol sorbitan esters include polyethylene glycol sorbitan monolaurate (Tween 20), polyoxyethylene sorbitan monopalmitate (Tween 40), polyethylene glycol sorbitan monostearate (Tween 60), and polyoxyethylene sorbitan monooleate (Tween 80). Examples of sorbitan esters include sorbitan monolaurate (Span 20), sorbitan monopalmitate (Span 40), sorbitan monostearate (Span 60), and sorbitan monooleate (Span 80).
[0084] FIG. 15 shows examples of encapsulating agents that form polyelectrolytes. Polyelectrolytes are macromolecules that have (multiple) charged groups covalently attached to them when dissolved in a polar solvent such as water. Based on charge (electrochemistry), polyelectrolytes are classified as polycations (polybases), polyanions (polyacids), and polyampholytes. Based on charge density, polyelectrolytes are classified as strong and weak polyelectrolytes. Strong polyelectrolytes spontaneously acquire a full charge, while weak polyelectrolytes only become partially charged upon dissociation. Examples of polyelectrolytes include alginate, chitosan, pectin, polydiallyldimethylammonium chloride, polyethyleneimine, polyacrylic acid, polysodium 4-styrenesulfonate, poly(2-dimethylamino)ethyl methacrylate)methyl chloride quaternary salt, poly(allylamine hydrochloride), and poly(diallyldimethylammonium chloride) solutions.
[0085] FIG. 16 shows examples of encapsulating agents that form liposomes. Liposomes are phospholipids that form micelles or vesicles in aqueous solution. A wide variety of substitution patterns of R1, R2, and R3 are known. For example, R1 can be H, ethanolamine, choline, serine, glycerol, etc. R1 and R2 are linear carbon chains having 8 to 18 carbons. The carbon chains can be saturated or unsaturated.
[0086] Examples of material additives include organic species that form oxygen radicals under reaction conditions, including ligands (capable of complexing with metal ions in a commercial CMP slurry and / or capable of complexing with the surface of the substrate being planarized), ligand-metal complexes (e.g., preformed complexes with metal ions other than those in the CMP slurry), and non-metallic ROS-generating catalysts.
[0087] Examples of ligands include salicylhydroxamic acid (SHA), suberohydroxamic acid, tert-butyl N-(benzyloxy)carbamate, bipyridyl, lysine, tryptophan, phenylalanine, tyrosine, ethylacetohydroxamate, hydroxycarbamide, benzhydroxamic acid, trans-cinnamic acid, adipic acid, and caproic acid. In some embodiments, the material additive is a ligand that is premixed with a metal ion (e.g., copper ion) in the solution to form a ligand-metal complex. Examples of metal ions include magnesium ion, calcium ion, barium ion, nickel ion, copper ion, zinc ion, strontium ion, iron ion, cobalt ion, titanium ion, vanadium ion, chromium ion, molybdenum ion, and manganese ion. These metals do not need to be used with a ligand and may be used alone.
[0088] FIG. 17 shows examples of ROS-generating catalysts that are non-metallic. Such ROS-generating catalysts generate ROS under reactive conditions (e.g., upon exposure to photons or sound waves). In one embodiment, the ROS-generating catalyst is an organic (i.e., hydrocarbon-containing) catalyst. In one embodiment, the ROS-generating catalyst is an aminooxy radical (i.e., nitroxyl radical). Examples of compounds that generate aminooxy radicals include OXANOH, HHTIO, HTIO, carboxy-PTIO-H (and its corresponding salts), piperidine-based TEMPO derivatives (e.g., TEMPOH derivatives, TEMPOL-H derivatives, TEMPONE-H derivatives), C 10 derivatives (TPL-H02 derivatives, TMH derivatives, TMTH derivatives, CAT1H derivatives, PPH derivatives, mitoTEMPO-H derivatives) and PROXYL derivatives. In each of these cases, the nitrogen of the nitroxyl radical is adjacent to a geminal alkyl group, such as a geminal methyl group. In yet another embodiment, the ROS generating catalyst is xanthine or hypoxanthine.
[0089] Below are a series of examples illustrating operations performed in accordance with the slurry processing techniques performed by a CMP slurry processing system, as described in one or more embodiments herein.
[0090] In one example, the wafer polishing apparatus shown in FIG. 1 has a concentric grooved pad on which at least one 300 mm blanket tungsten wafer is placed. The polishing time is configured to be 45 seconds. The slurry includes Versum DP1142-1 with 2% H2O2. Another exemplary slurry formulation may include, but is not limited to, 1.0 wt% glycine, 0.5 wt% 60 nm SiO2, 100 ppm BTA, 1.0 wt% H2O2, and has a pH=5.8. Another exemplary slurry formulation may include, but is not limited to, 1.0 mM hydroquinone and 1.0 wt% calcined ceria, and has a pH of 4.0. Another exemplary slurry formulation may include, but is not limited to, an in-house formulation including 1.0 mM glutamic acid and 1.0 wt% calcined ceria, and has a pH of 4.0.
[0091] In another embodiment, the slurry injection system 800 shown in FIG. 8 is configured to process slurry at a flow rate of 125 mL / min. The polishing pad 103 rotates at 70 RPM with a sinusoidal sweep schedule of 10 sweeps per second. A downward force of 7 pounds is applied to the disk. A break-in period of 45 minutes occurs with a pad rotation speed of 80 RPM. The ex situ conditioning process occurs for 30 seconds. The conventional and inventive distribution systems are configured to apply a polishing pressure of 4 PSI. The sliding speed is 1.6 meters / second. The power intensity provided by both the conventional slurry distribution system and the slurry processing device 400 is configured to be 20 W.
[0092] As described above, the CMP slurry processing system 10 can include a light wave energy source that is part of a polishing operation on a substrate 20 formed from copper, tungsten, silicon carbide, silicon dioxide, or combinations or alloys thereof, and / or other substrate materials used in shallow trench isolation (STI) CMP applications that require the use of a slurry. In some embodiments, the CMP application includes a plasma enhanced tetra-ethoxyorthosilicate (PE-TEOS) SiO2 CMP process. In some embodiments, a light activated slurry for STI CMP can be provided by utilizing a ligand-to-metal charge transfer LMCT mechanism between a complex additive and CeO2 nanoparticles, which in turn can enhance the removal rate during the CMP process. The additive containing the ligand allows for the transfer of electrons from the ligand to the metal surface of the substrate, resulting in the reduction of metal ions by the ligand.
[0093] In another embodiment, ligand complexing agents such as tyrosine (Tyr), phenylalanine (Phe), tryptophan (Trp), histidine (HID), and glycine (Gly) bind to metal ions, etc., on the metal oxide surface of the substrate, resulting in the formation of a metal oxide-ligand complex. Irradiation of this complex, for example by lightwave energy source 112 of Figures 9A-9C, excites electrons from the coordinated carboxylate groups, which then transfer to the conduction band (CB) of CeO2. This then causes the CeO2 to undergo oxidation. 4+ Ce 3+ and desorbs surface O2, thus increasing the availability of oxygen vacancies for nucleophilic attack. Additionally, throughout the process, the ligands are oxidized, preventing re-adsorption onto the nanoparticles, enhancing the available surface area. Thus, the increased surface activity, i.e., available oxygen vacancies, enhances the oxide removal rate during the polishing operation.
[0094] In another example, the slurry processing technique may include polymer-based nanocomposite slurries formed by the incorporation of macromolecular polymers, such as, but not limited to, alginate and pectin, along with composite-forming additives. Such material additives provide a dual function within the composite, namely, (1) to crosslink the polymer matrix, and (2) to incorporate itself into the self-cleaning / pressure-responsive core. The composite additives may include, but are not limited to, common rate-accelerating additives, such as glycine (Gly), L-serine (Ser), itaconic acid (Itac), oxalic acid (Ox), succinic acid (Succ), and hydroquinone (HQ). Additionally, photoreactive derivatives of molecules such as azobenzene, cyclodextrin, Schiff base ligands, spiropyrans, and polyamines may be integrated, either covalently or non-covalently, onto the outer surface of the polymer composite to provide controlled release of rate-enhancing additives upon irradiation and enhance the removal of contaminants, i.e., metal ions and / or organometallic complex residues. Covalently attached photoactive functional groups derived from this class of molecules can undergo switchable isomerization when irradiated with ultraviolet, visible, or infrared light from a light generating system or related energy source described in embodiments herein. Additionally, when irradiated with specific wavelengths of light, the material additives possess rate enhancing properties that control the removal rate of the substrate in situ.
[0095] According to some embodiments, the removal rate of a SiC substrate can be enhanced by using megasonic energy, in which case acoustic and optical waves are applied, either alone or in combination, via a polishing apparatus such as that shown in FIG.
[0096] More specifically, the reactive chemistry that results from one or more of the techniques described with respect to the embodiments herein, in the pre-sonication state, can act on the film formation rate on the SiC substrate, resulting in the formation of an abrasive layer. This layer can be soft, but also dense. Thus, a significant amount of mechanical energy (i.e., high values of pressure and sliding speed) is required to remove the soft passivation layer and remove the surface topography through abrasive action. Upon exposure to ultrasonication, there is a shift in dynamic equilibrium at the substrate surface due to the release of additives and the generation of increased critical reactive oxygen species (ROS). Such additives reduce the density of the surface passivation film, resulting in a "softer" and less mechanically dependent interaction. This then results in a faster removal rate at lower values of operating pressure and sliding speed. The combination of these paired systems, i.e., slurry formulations and megasonic energy generation, can result in a synergistic improvement that significantly increases material removal rates while minimizing process time, improving defect levels (due to less mechanical action required), and maximizing consumable life.
[0097] The following is an exemplary series of experiments comparing one or more of the above-mentioned wafer polishing techniques with the absence of ultrasonication or other wave application and with sonic and / or light waves applied to the polishing slurry. Here, an internally formulated bulk copper slurry containing colloidal silica nanoparticles (NPs), water, hydrogen peroxide, a copper chelator (such as glycine), and a copper passivator (such as benzotriazole) is used for the experiments. A concentrically grooved pad, e.g., a Dupont IC1000® pad, is positioned on a 200 mm rotating platen. A 3M (S60-AI) diamond conditioning disk is used in ex situ conditioning mode for 1 minute. A copper metal substrate having a diameter of 25 mm and a thickness of 18 mm is polished. The process pressure ranges from 1 to 5 PSI. The sliding speed ranges from 0.25 to 1.05 m / sec. The slurry flow rate ranges from 25 to 100 cc / min. The applied sonic energy ranged from 0 to 2.0 watts / cm2 After polishing a total of 90 copper substrates, and depending on the process conditions, the observed copper removal rates ranged from 0 watts / cm to 100 watts / cm for sonic energy of zero (0) watts / cm. 2 (i.e., without any sonication) ranges from 1,061 to 4,270 Å / min. 2 In contrast, copper removal rates based on polishing another 90 wafers ranged from 1,207 to 6,219 Angstroms / min. For comparison, tests without ultrasonic treatment at process conditions of 5 PSI pressure, 0.65 m / sec sliding velocity, and 100 cc / min flow rate produced an average copper removal rate of 3,558 Angstroms / min. Conversely, at 1.5 Watts / cm 2 Tests with an ultrasonic energy of 1000 Å resulted in an average removal rate value of 6,219 Å / min copper removal rate. This represented a 43% increase in copper removal rate with sonication. With slurry sonication, there is zero incubation time for the slurry in the continuous flow sonicator. That is, the slurry does not remain stagnant or in any kind of holding pattern within the reactor for any period of time. Rather, the slurry is continuously sonicated while it flows through and towards the polisher.
[0098] In another example, a commercially available copper slurry, Fujimi Corporation PL-7106®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is used. Additionally, a 3M (S60-AI) diamond conditioning disk is used in ex situ conditioning mode for 1 minute. Copper metal substrates having a diameter of 25 mm and a thickness of 18 mm are polished. The applied process pressure ranges from 1 to 5 PSI. The sliding speed ranges from 0.25 to 1.05 m / sec. The slurry flow rate ranges from 25 to 100 cc / min. After polishing 90 copper substrates, depending on the process conditions, the observed copper removal rates range from 1,127 to 6,325 angstroms / min without ultrasonic treatment. 1.5 Watts / cm2 After polishing another 90 wafers, the copper removal rates range from 1,578 to 6,723 Å / min. For comparison, at process conditions of 5 PSI pressure, 1.05 m / sec sliding velocity, and 62.5 cc / min flow rate, without ultrasonic treatment, results include an average copper removal rate of 6,325 Å / min, while at 1.5 watts / cm 2 At a sonication energy of 1.0 MPa, an average copper removal rate of 6,723 Angstroms / min is observed. This corresponded to a 6% increase in copper removal rate with sonication. In the case of slurry sonication, there is zero incubation time of the slurry in the continuous flow sonicator. That is, the slurry does not remain stagnant or in any kind of holding pattern within the reactor for any period of time. Rather, the slurry is continuously sonicated while flowing through and towards the polisher. Further corroborating evidence is seen at electrode rotation speeds equivalent to process conditions of 1 PSI and 0.25 m / sec. In this case, there is clear evidence of a shift in corrosion with no sonication, measured at 1.45 microamps. Whereas at 1.5 Watts / cm 2 For sonication, the pressure increased to 18.6 microamps.
[0099] In another example, a commercially available tungsten slurry, Cabot Microelectronics Corporation SSW7300®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is also used. Additionally, a 3M (S60-Al) diamond conditioning disk is used in ex situ conditioning mode for 1 minute. A tungsten metal substrate having a diameter of 25 mm and a thickness of 18 mm is polished. The applied process pressure is in the range of 1-5 PSI. The sliding speed is in the range of 0.25-1.05 m / sec. The slurry flow rate is in the range of 25-100 cc / min. The sonic energy is in the range of 0-1.5 Watts / cm. 2After polishing 90 tungsten substrates, depending on the process conditions, observed tungsten removal rates range from 1,812 to 2,170 Å / min without ultrasonic treatment and 1.5 watts / cm 2 After polishing another 90 wafers, the tungsten removal rates range from 2,204 to 2,712 Angstroms / min. For comparison, tests without ultrasonic treatment had an average tungsten removal rate of 2,129 Angstroms / min at process conditions of 5 PSI pressure, 1.05 m / sec sliding velocity, and 62.5 cc / min flow rate. 2 An average removal rate of 2,712 Angstroms / min was observed, which represents a 27% increase. With slurry sonication, there is zero incubation time for the slurry in the continuous flow sonicator. That is, the slurry does not remain stagnant or in any kind of holding pattern within the reactor for any period of time. Rather, the slurry is continuously sonicated while it flows through and towards the polisher.
[0100] In another example, a commercial bulk copper slurry, Versum Materials CoppeReady3930®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is used. A 3M (S60-AI) diamond conditioning disk is used in ex situ conditioning mode for 1 minute. A copper metal substrate having a diameter of 25 mm and a thickness of 18 mm is polished. The process pressure is in the range of 1-5 PSI. The sliding speed is in the range of 0.25-1.05 m / sec. The slurry flow rate is in the range of 25-100 cc / min. The sonic energy settings are between 0 and 1.5 watts / cm. 2 After polishing 90 copper substrates, depending on the process conditions, the observed copper removal rates range from 2,307 to 9,043 Å / min with the ultrasonic treatment turned off and 1.5 watts / cm. 2After polishing another 90 wafers, the copper removal rates range from 2,519 to 13,512 Angstroms / min. For comparison, at process conditions of 5 PSI pressure, 0.65 m / sec sliding speed and 100 cc / min flow rate, no ultrasonic treatment resulted in an average copper removal rate of 9,043 Angstroms / min, while 1.5 Watts / cm 2 At a sonication energy of 1000 Å, an average copper removal rate of 13,512 Å / min is observed. This represents a 49% increase. In the case of slurry sonication, there is zero incubation time of the slurry in the continuous flow sonicator. That is, the slurry does not remain stagnant or in any kind of holding pattern within the reactor for any period of time. Rather, the slurry is continuously sonicated while it flows through and towards the polisher.
[0101] In another example, a commercially available bulk copper slurry, Versum Materials CoppeReady3930®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. Also, a Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is used with a 3M (S60-AI) diamond conditioning disk in ex situ conditioning mode for 1 minute. A copper metal substrate having a diameter of 25 mm and a thickness of 18 mm is polished. The process pressure is in the range of 1-5 PSI. The sliding velocity values are 0.25-1.05 m / sec. The slurry flow rate is 25-100 cc / min. The sonic energy settings are 0.5, 1.5, or 2.0 watts / cm. 2 After polishing 20 copper substrates, depending on the process conditions, the observed copper removal rates ranged from 0.5 watts / cm for ultrasonic treatment energy to 0.5 watts / cm for ultrasonic treatment energy. 2 When the ultrasonic treatment energy was set at 1.5 Watts / cm, the observed copper removal rates ranged from 5,563 to 11,504 Å / min. After polishing 20 additional copper substrates, depending on the process conditions, the observed copper removal rates ranged from 5,563 to 11,504 Å / min when the ultrasonic treatment energy was set at 1.5 Watts / cm. 2When the ultrasonic treatment energy was set at 2.0 Watts / cm, the observed copper removal rates ranged from 5,789 to 11,377 Å / min. Furthermore, after polishing 20 copper substrates, depending on the process conditions, the observed copper removal rates ranged from 5,789 to 11,377 Å / min when the ultrasonic treatment energy was set at 2.0 Watts / cm. 2 The results range from 2,238 to 7,118 Å / min when sonication energies were set at 0.5 to 2.0 Watts / cm 2 showed that when the sonication was increased to 20 watts, the average copper removal rate decreased by 40%. However, when the sonication was further increased to 30 watts, the average copper removal rate dropped by 10% from as high as 23 watts. In the case of slurry sonication, there is zero incubation time of the slurry in the continuous flow sonicator. That is, the slurry does not remain stagnant or in any kind of holding pattern in the reactor for any period of time. Rather, the slurry is continuously sonicated while flowing through and towards the polisher. This showed that higher sonication energy is not necessarily better for removal rate, at least when polishing small substrates.
[0102] In another example, a commercial high velocity copper slurry, Versum Materials CoppeReady3935®, mixed with water and hydrogen peroxide (per manufacturer's specifications), and a Dupont IC1000® concentric grooved pad on a 200 mm rotating platen and a 3M (S60-AI) diamond conditioning disk for 1 minute in ex situ conditioning mode is used. A copper metal substrate having a diameter of 25 mm and a thickness of 18 mm is polished. The process pressure ranges from 1 to 5 PSI. The sliding speed ranges from 0.25 to 1.05 m / sec. The slurry flow rate ranges from 25 to 100 cc / min. The sonic energy settings are 0, 0.5, and 1.5 watts / cm. 2 After polishing 14 copper substrates, depending on the process conditions, the observed copper removal rates range from 2,069 to 9,512 Å / min without sonication. After polishing another 14 copper substrates, depending on the process conditions, the observed copper removal rates range from 2,069 to 9,512 Å / min with sonication energy of 0.5 watts / cm.2 When the ultrasonic treatment energy was set at 1.5 Watts / cm, the observed copper removal rates ranged from 2,360 to 9,741 Å / min. After polishing another 14 copper substrates, depending on the process conditions, the observed copper removal rates ranged from 2,360 to 9,741 Å / min when the ultrasonic treatment energy was set at 1.5 Watts / cm. 2 The results range from 2,586 to 8,858 Å / min when sonication energies were set at zero to 0.5 Watts / cm. 2 However, when ultrasonic treatment was increased from 0.5 to 1.5 watts / cm, the average copper removal rate increased by 10%. 2 Further increasing the watts / cm2 increases the average copper removal rate to 0.5 watts / cm2. 2 Dynamic electrochemical analysis results performed under the same pressure, slurry flow rate, and velocity as the polishing conditions above showed that the corrosion current ranged from 1.29 to 4.34 microamps when the sonication energy was set to 0.5 watts / cm. 2 At sonication energies of 1.5 Watts / cm, the corrosion current increased to be in the range of 1.34 to 5.20 microamperes. However, at 1.5 Watts / cm 2 At a sonication energy of 0.56-3.22 microamps, the corrosion currents decreased from their high values and ranged from 0.56-3.22 microamps. The trend in the corrosion current results is consistent with the trend in the removal rates. For slurry sonication, there is zero incubation time of the slurry in the continuous flow sonicator. That is, the slurry does not remain stagnant or in any kind of holding pattern within the reactor for any period of time. Rather, the slurry is continuously sonicated while it flows through and towards the polisher.
[0103] In another example, a commercially available barrier slurry, Versum Materials Barrier 6250®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Fujibo H800® embossed pad on a 200 mm rotating platen is also used, with a 3M (PB33A-1) bristle brush conditioning disk used in ex situ conditioning mode for 1 minute. A tantalum metal substrate having a diameter of 25 mm and a thickness of 18 mm is polished. The process pressure ranges from 1 to 5 PSI. The sliding speed ranges from 0.25 to 1.05 m / sec. The slurry flow rate is held constant at 62.5 cc / min. The sonic energy settings are 0, 0.5 or 1.5 watts / cm. 2 After polishing 14 tantalum substrates, depending on the process conditions, the observed tantalum removal rates range from 250 to 830 Å / min without sonication. After polishing another 14 tantalum substrates, depending on the process conditions, the observed tantalum removal rates range from 250 to 830 Å / min with sonication energy of 0.5 Watts / cm 2 When the ultrasonic treatment energy was set at 1.5 Watts / cm, the observed tantalum removal rates ranged from 380 to 810 Å / min. After polishing another 14 tantalum substrates, depending on the process conditions, the observed tantalum removal rates ranged from 1.5 Watts / cm 2 The results range from 496 to 1,045 Å / min when sonication energies were set at zero to 0.5 Watts / cm. 2 The results showed that the average tantalum removal rate increased by 20% when the ultrasonic treatment energy was increased to 1.5 Watts / cm 2 Further increasing the tantalum removal rate to 0.5 Watts / cm 2 This is an additional 10% increase from its value in
[0104] In another example, a commercially available barrier slurry, Versum Materials Barrier 6250®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Fujibo H800® embossed pad on a 200 mm rotating platen is also used, with a 3M (PB33A-1) bristle brush conditioning disk used in ex situ conditioning mode for 1 minute. A copper metal substrate having a diameter of 25 mm and a thickness of 18 mm is polished. The process pressure ranges from 1 to 5 PSI. The sliding speed ranges from 0.25 to 1.05 m / sec. The slurry flow rate is kept constant at 62.5 cc / min. Sonic energy is applied at 0, 0.5 or 1.5 Watts / cm. 2 After polishing 14 copper substrates, depending on the process conditions, the observed copper removal rates range from 371 to 635 Å / min without sonication. After polishing another 14 copper substrates, depending on the process conditions, the observed copper removal rates range from 371 to 635 Å / min with sonication energy of 0.5 Watts / cm. 2 When the ultrasonic treatment energy was set at 1.5 Watts / cm, the observed copper removal rates ranged from 497 to 1,016 Å / min. After polishing another 14 copper substrates, depending on the process conditions, the observed copper removal rates ranged from 497 to 1,016 Å / min when the ultrasonic treatment energy was set at 1.5 Watts / cm. 2 The results range from 583 to 1,219 Å / min when sonication energies were set at zero to 0.5 Watts / cm 2 The average copper removal rate increased by 40% when ultrasonic treatment was increased to 1.5 watts / cm 2 Further increasing the watts / cm2 increases the average copper removal rate to 0.5 watts / cm2. 2 This is an additional 15% increase from the initial average value at 0 watts / cm 2 At 1.5 Watts / cm, the average copper to tantalum removal rate selectivity is 1.04:1. 2In this case, the average copper to tantalum removal rate selectivity is 1.18:1. In the case of slurry sonication, there is zero incubation time for the slurry in the continuous flow sonicator. That is, the slurry does not remain stagnant or in any kind of holding pattern within the reactor for any period of time. Rather, the slurry is continuously sonicated while it flows through and towards the polisher.
[0105] The following examples include applications of the above-described process, including light-activated or sound-activated chemical additives.
[0106] In one embodiment, sonic activation chemicals can be added to pre-made slurries, specifically, an internally compounded slurry consisting of calcined cerium nanoparticles and redox additives for shallow trench isolation (STI) CMP applications is prepared. The material additives are selected based on their functionality. Glutamic acid has a carboxylic acid functionality known to inhibit oxide removal, while hydroquinone, with a hydroxyl functionality, is known to promote oxide removal. A Dupont IC1000® concentric grooved pad on a 200 mm rotating platen and a 3M (S60-AI) diamond conditioning disk are used in ex-situ conditioning mode for 1 minute. A 1-inch diameter silicon wafer with a tetraethyl orthosilicate (TEOS) based silicon dioxide film deposited thereon is used for polishing. The process pressure ranges from 0.5 to 1.5 PSI. The sliding speed is kept constant at 0.52 m / sec. The slurry flow rate is kept constant at 75 cc / min. Without ultrasonic treatment, TEOS wafer removal rates are observed to range from 3,652 to 6,008 Å / min at 1.0 mmol of hydroquinone and 1.5 Watts / cm. 2With sonication at 1.0 mmol / cm, TEOS wafer removal rates are observed to range from 3,124 to 7,587 Å / min at 1.0 mmol / cm hydroquinone. This corresponded to a 10% decrease at low sonication, but an average increase of 12% with increasing sonication power. Without sonication, TEOS wafer removal rates are observed to range from 3,558 to 5,876 Å / min at 1.0 mmol / cm glutamic acid. 2 For sonication at 1.0 mmol of glutamic acid, the TEOS wafer removal rates are observed to range from 3,611 to 7,831 Angstroms / min at 1.0 mmol of glutamic acid. This represented an average increase of 10%. For slurry sonication, there is zero incubation time for the slurry in the continuous flow sonicator. That is, the slurry does not remain stagnant or in any kind of holding pattern within the reactor for any period of time. Rather, the slurry is continuously sonicated while it flows through and towards the polisher.
[0107] In another embodiment, an internal compounding slurry for shallow trench isolation (STI) CMP applications is prepared by utilizing the ligand-to-metal charge transfer (LMCT) mechanism between a complexing additive and ceria (colloidal or calcined) nanoparticles (NPs). More specifically, ligands such as tyrosine (Tyr), phenylalanine (Phe), tryptophan (Trp), histidine (His), and glycine (Gly) tend to form complexes with metal oxide surfaces via coordinate bonds, resulting in the formation of complexes between metal oxide (MOX) and the ligands. When this complex is irradiated (with light wavelengths in the range of 250-800 nm), electrons from the coordinated carboxylate groups are excited and ultimately transferred to the conduction band (CB) of the ceria NPs. This, in turn, results in the formation of Ce. 4+ Ce 3+, which reduces the surface O2 and desorbs the surface O2, thereby increasing the availability of oxygen vacancies for nucleophilic attack. Furthermore, throughout the process, the ligands are oxidized, thus preventing re-adsorption onto the nanoparticles, enhancing the available surface area. Thus, the increased surface activity (i.e., available oxygen vacancies) significantly enhances the oxide removal rate. The experimental procedure allowed the slurry to be pumped through clear acrylic tubing. Thus, the slurry can be illuminated via either laser light or light through a series of LED arrays. For example, the clear pipe section is an acrylic tubing with an inside diameter (ID) of approximately 2 inches and a length of 18 inches. The tubing is enclosed within a 16.4 foot LED strip consisting of 300 individual LEDs. The wavelength of the strip ranges from 250 to 800 nm. An internally compounded STI slurry is prepared using calcined ceria NPs dispersed in water. Tyrosine is then added to the slurry for effective charge transfer. A Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is used. A 3M (model) diamond conditioning disk is also used in ex situ conditioning mode for 1 minute. One inch diameter silicon wafers with silicon dioxide deposited (using tetraethyl orthosilicate as a precursor) are used for polishing. The process pressure ranges from 1 to 5 PSI. The sliding speed ranges from 0.25 to 1.05 m / sec. The slurry flow rate is kept constant at 75 cc / min. After polishing the silicon dioxide wafer, the film removal rate is observed to be in the range of 2,753 to 3,109 Angstroms / min without illumination. After polishing another 20 silicon dioxide wafers, the film removal rate is observed to be in the range of 2,948 to 3,650 Angstroms / min with illumination using a 520 to 525 nanometer green LED. This corresponds to an average increase of 10%.
[0108] In another example, a commercial bulk copper slurry, Versum Materials CoppeReady3930®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. Also, a Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is used with a 3M (S60-AI) diamond conditioning disk in ex situ conditioning mode for 1 minute. The copper metal substrate used for polishing had a diameter of 25 mm and a thickness of 18 mm. The process pressure was 3 PSI, the sliding speed was 0.79 m / sec, and the slurry flow rate was kept constant at 65 cc / min. Sonic energy was applied at 0 or 1.5 Watts / cm2. 2 After polishing 10 copper substrates, the average copper removal rate observed is 2,609 Angstroms / min without sonication. After polishing another 6 copper substrates, the slurry is set at 1.5 Watts / cm without any incubation. 2 When the slurry was sonicated at 1.5 watts / cm, the average copper removal rate observed was 3,623 Angstroms / min. After polishing seven additional copper substrates, the average copper removal rate observed was 3,623 Angstroms / min. 2 When sonicated at 100 Å / min, the mean fluence was 4,258 Å / min, but after a 1-minute incubation, which represented a 39% increase between no sonication and sonication with a 1-minute incubation.
[0109] In another embodiment where the sonoactivation chemicals are added to a pre-made slurry, alumina (spherical or ellipsoidal) NPs, water, hydrogen peroxide, and an organometallic complex (i.e., Cu +2An internally formulated silicon carbide CMP slurry consisting of 10 ... 2 The silicon side of the silicon carbide substrate is polished using a hydrogen peroxide-based formulation containing an electrophilic enhancer. Depending on the process conditions, the observed removal rates range from 0 watts / cm to 10 watts / cm of ultrasonic treatment energy. 2 When set at 1.5 watts / cm, the range is 1,223 to 1,792 nm / hour. 2 In the 300-3500 series, silicon carbide removal rates range from 2,764 to 4,122 nm / hr. These represent an average increase of 58%. For slurry sonication, the incubation time of the slurry in the continuous flow sonicator is 5 minutes. That is, the slurry does not remain stagnant or in any kind of holding pattern in the reactor for any period of time. Rather, the slurry is continuously sonicated while it flows through and towards the polisher. The foregoing includes the addition of sonic activation chemicals to pre-made slurries.
[0110] In another example, a commercial bulk copper slurry, Versum Materials CoppeReady3930®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used for polishing. A Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is used. Also, a 3M (S60-AI) diamond conditioning disk is used in ex situ conditioning mode for 1 minute. A copper metal substrate having a diameter of 25 mm and a thickness of 18 mm is used for polishing. The process pressure is in the range of 1-5 PSI. The sliding speed is 0.25-1.05 m / sec. The slurry flow rate is in the range of 65-120 cc / min. Sonic energy is 1.5 Watts / cm with an incubation time of 1 minute. 2 The pressure was kept constant at 100 psi. After polishing ten copper substrates with a slurry flow rate of 65 cc / min, the observed copper removal rates ranged from 3,433 to 5,132 Å / min. After polishing ten copper substrates with a slurry flow rate of 120 cc / min, the observed copper removal rates ranged from 3,713 to 6,020 Å / min. In all cases, higher pressures resulted in higher removal rates. Also, higher flow rates increased the removal rate by an average of 10%.
[0111] In another example, a commercial bulk copper slurry, Versum Materials CoppeReady3930®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is also used. A 3M (S60-AI) diamond conditioning disk is also used in ex situ conditioning mode for 1 minute. A copper metal substrate having a diameter of 25 mm and a thickness of 18 mm is polished. The process pressure ranges from 1 to 5 PSI. The sliding speed ranges from 0.25 to 1.05 m / sec. The slurry flow rate is kept constant at 65 cc / min. The sonication energy settings are 0, 0.5, 1, 1.5, and 2 Watts / cm. 2In all cases, a 1 minute incubation time is used. After polishing 10 copper substrates, the average copper removal rate observed is approximately 2,572 Angstroms / min without ultrasonic treatment. The removal rate is approximately 0.5 Watts / cm 2 At 100 nm, the sonication energy increased to a maximum average value of 4,959 Å / min, and then increased to 1, 1.5, and 2 Watts / cm 2 As the removal rate increases to 4,455, 3,845, and 3,500 Å / min, respectively, it steadily decreases, indicating that the possibility of over-oxidation (i.e., increased reactive oxygen species) altering the passivation complexation properties at the copper surface may be detrimental to the removal rate.
[0112] In another example, a commercial bulk copper slurry, Versum Materials CoppeReady3930®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is used. A 3M (S60-AI) diamond conditioning disk is used in ex situ conditioning mode for 1 minute. The copper metal substrate used for polishing has a diameter of 25 mm. The process pressure is 3 PSI, the sliding speed is 0.52 m / sec, and the slurry flow rate is kept constant at 65 cc / min. After polishing, an atomic force microscope is used to analyze the copper surface. Without ultrasonic treatment, the average wafer surface roughness (Ra) is 1.1 nm. With sonic energy of 2.0 Watts / cm 2 When the SiO2 concentration is set at 0.05, the average wafer surface roughness (Ra) decreases to 0.78 nm, which represents a 29% improvement in reducing the surface roughness.
[0113] In another example, a commercially available tungsten slurry, Versum Materials DP1236®, mixed with hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® concentric grooved pad on a 200 mm rotating platen is used. A 3M (S60-AI) diamond conditioning disk is operated in ex situ conditioning mode for 1 minute. The tungsten substrate is polished with a polishing pressure of 3 PSI, a sliding speed of 0.52 m / sec, and a slurry flow rate of 65 cc / min. After polishing, an atomic force microscope is used to analyze the surface of the tungsten substrate. Without ultrasonic treatment, the average wafer surface roughness (Ra) is 1.07 nm. Sonic energy is 2.0 Watts / cm 2 When the annealing temperature is set at 0.5°C, the average wafer surface roughness (Ra) decreases to 0.88 nm, which represents an 18% improvement in reducing the surface roughness.
[0114] The following examples include large (200 mm) wafer polishing, with and without sonication, as described in the embodiments above.
[0115] In one embodiment, a commercially available copper slurry, Versum Materials CoppeReady3930®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. Additionally, a Dupont IC1010® concentric grooved pad on an 800 mm rotating platen is used. A Saesol 4DNS80AMC1 diamond conditioning disk is used in in-situ conditioning mode. 200 mm blanket copper wafers are polished for 30 seconds per wafer. Process pressure ranges from 1.5 to 2.0 PSI. Slide speed is set at 1.5 m / sec. Slurry flow rate is held constant at 150 cc / min. Sonic energy settings are 1 Watt / cm with an incubation time of 15 minutes. 2Each combination of polishing conditions is run in duplicate. At a polishing pressure of 1.5 PSI, the average copper removal rates are 8,599 and 9,629 Angstroms / min for the process without and with ultrasonic treatment, respectively. This represents a 12% increase in removal rate. At a polishing pressure of 2.0 PSI, the average copper removal rates are 10,975 and 12,223 Angstroms / min for the process without and with ultrasonic treatment, respectively. This represents an 11% increase in removal rate.
[0116] In another example, a commercial copper slurry, Versum Materials CoppeReady3930®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1010® concentric grooved pad on an 800 mm rotating platen and a Saesol 4DNS80AMC1 diamond conditioning disk are used in in-situ conditioning mode. 200 mm blanket copper wafers are polished for 30 seconds per wafer. Process pressures range from 1.5 to 2.0 PSI. Slide speed is kept constant at 1.5 m / sec. Slurry flow rate is also held constant at 150 cc / min. Without ultrasonic treatment, the average copper removal rates are 9,372 and 11,919 Angstroms / min at polishing pressures of 1.5 and 2.0 PSI, respectively. Sonic energy is applied at 0.5 Watts / cm 2 With a polishing pressure of 1.0 PSI and an incubation time of 15 minutes, the copper removal rate at a polishing pressure of 2.0 PSI increased to 12,260 Å / min, representing a 3% increase in removal rate. 2 At a sonic energy setting of 1.5 Watts / cm, and again with an incubation time of 15 minutes, the average copper removal rates are 9,660 and 13,314 Angstroms / min at polishing pressures of 1.5 and 2.0 PSI, respectively. This represents a 3 and 12% increase in removal rate compared to the process without ultrasonic treatment. 2With a polishing pressure of 1.5 and 2.0 PSI and an incubation time of 5 minutes, the copper removal rates are 9,704 and 13,026 Å / min at polishing pressures of 1.5 and 2.0 PSI, respectively, which represent a 4 and 9% increase in removal rate compared to the process performed without ultrasonic treatment.
[0117] In another example, a commercial copper slurry, Versum Materials CoppeReady3930®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1010® concentric grooved pad on an 800 mm rotating platen is also used. A Saesol 4DNS80AMC1 diamond conditioning disk is also used in in-situ conditioning mode. 200 mm blanket copper wafers are polished for 30 seconds per wafer. Process pressures range from 1.5 to 2.0 PSI. Slide speed is set at 1.5 m / sec. Slurry flow rate is held constant at 150 cc / min. Without ultrasonic treatment, the average copper removal rates based on a total of six wafers polished are 8,403 and 11,006 Angstroms / min at polishing pressures of 1.5 and 2.0 PSI, respectively. 1.0 Watts / cm 2 At an ultrasonic energy setting of 2.0 Watts / cm and an incubation time of 5 minutes, the copper removal rates based on a total of four wafers polished increase to 8,806 and 11,789 Angstroms / min at polishing pressures of 1.5 and 2.0 PSI, respectively. This represents a 5 and 7% increase in average removal rate compared to the process without ultrasonic treatment. 2 With an incubation time of 5 minutes, the average copper removal rate based on a total of four wafers polished also increased to 9,134 and 12,075 Å / min at polishing pressures of 1.5 and 2.0 PSI, respectively, which represents a 9 and 10% increase in removal rate compared to the process without ultrasonic treatment.
[0118] In another example, a commercial copper slurry, Versum Materials CoppeReady3935®, mixed with water and hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1010® concentric grooved pad on an 800 mm rotating platen is also used. A Saesol 4DNS80AMC1 diamond conditioning disk is also used in in-situ conditioning mode. 200 mm blanket copper wafers are polished for 30 seconds per wafer. Process pressures range from 1.5 to 2.0 PSI. Slide speed is set at 1.5 m / sec. Slurry flow rate is held constant at 150 cc / min. Without ultrasonic treatment, the average copper removal rates based on a total of four wafers polished are 8,365 and 10,748 Angstroms / min at polishing pressures of 1.5 and 2.0 PSI, respectively. Sonic energy is 2.0 Watts / cm 2 and again with an incubation time of 5 minutes, the average copper removal rate based on a total of four wafers polished increased to 9,017 and 12,066 Angstroms / min at polishing pressures of 1.5 and 2.0 PSI, respectively, which represents an 8 and 12% increase in removal rate compared to the process without ultrasonic treatment.
[0119] In another example, a tungsten slurry, Versum Materials DP1236®, mixed with hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® XY grooved pad on an 800 mm rotating platen is used. A Saesol 4DNS80AMC1 diamond conditioning disk is also used in ex situ conditioning mode for 30 seconds before each wafer polish. 200 mm blanket tungsten wafers are polished for 60 seconds per wafer. The process pressure is 4.0 PSI. The sliding speed is set at 2.0 m / sec. The slurry flow rate is held constant at 125 cc / min. Without sonication, the average tungsten removal rate based on a total of 6 wafers polished is 2,277 Angstroms / min. Sonic energy is set at 2.0 Watts / cm 2With a setting of 0.05% and a 5 minute incubation time, the tungsten removal rate based on a total of six wafers is 2,423 Angstroms / min, which represents a 7% increase in removal rate.
[0120] In another example, a tungsten slurry, Versum Materials DP1236®, mixed with hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® XY grooved pad on an 800 mm rotating platen is used. A Saesol 4DNS80AMC1 diamond conditioning disk is also used in ex situ conditioning mode for 30 seconds before each wafer polish. 200 mm blanket tungsten wafers are polished for 60 seconds per wafer. The process pressure is 3.0 PSI. The sliding speed is set at 1.6 m / sec. The slurry flow rate is held constant at 125 cc / min. Without sonication, the average tungsten removal rate based on a total of four wafers polished is 1,646 Angstroms / min. Sonic energy is set at 2.0 Watts / cm 2 and again with a 5 minute incubation time, the average tungsten removal rate based on a total of four wafers polished is 1,803 Angstroms / min. This represents a 10% increase in removal rate.
[0121] In another example, a tungsten slurry, Versum Materials DP1142®, mixed with hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® XY grooved pad on an 800 mm rotating platen is used. A Saesol 4DNS80AMC1 diamond conditioning disk is operated in ex-situ conditioning mode for 30 seconds before each wafer polish. One or more 200 mm blanket tungsten wafers are polished for 45 seconds per wafer. The process pressure is kept constant at 4.0 PSI. The sliding speed is also kept constant at 1.6 m / sec. The slurry flow rate is held constant at 125 cc / min. Without sonication, the tungsten removal rate is 1,928 Angstroms / min. For slurry sonication, the slurry is sonicated continuously while it flows inside a tube that passes through the sonicator bowl and towards the polisher. The incubation time of the slurry in the continuous sonicator is estimated to be less than 10 seconds, i.e., the slurry does not remain stagnant or in any kind of holding pattern within the reactor for any period of time. The sonic energy setting was 1.25 Watts / cm 2 , the average tungsten removal rate is 2,112 Angstroms / min. This represents a 10% increase in removal rate.
[0122] In another example, a copper slurry, Versum Materials Cu3930®, mixed with hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® XY grooved pad on a 500 mm rotating platen is used. A Saesol 4DNS80AMC1 diamond conditioning disk is also used in ex-situ conditioning mode for 30 seconds before each wafer polish. A 200 mm blanket copper wafer is polished for 60 seconds per wafer. The process wafer pressure and the retaining ring pressure are kept constant at 1.5 and 1.7 PSI, respectively. The sliding speed is also kept constant at 0.5 m / sec. The slurry flow rate is kept constant at 160 cc / min. Without sonication, the copper removal rate is 4,909 Angstroms / min. For the polishing process with slurry sonication, two sonicator bowls are used in parallel with a slurry flow rate of 80 cc / min per bowl, resulting in a total slurry flow rate of 160 cc / min. Sonic energy in each sonicator bowl was set at 2.0 watts / cm 2 With a setting of 0.05% and an incubation time of 5 minutes, the average copper removal rate increased to 6,221 Å / min, which represents a 27% increase in removal rate compared to the process without sonication.
[0123] In another example, a copper slurry, Versum Materials Cu3930®, mixed with hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® XY grooved pad on a 500 mm rotating platen is used. A Saesol 4DNS80AMC1 diamond conditioning disk is also used in ex-situ conditioning mode for 30 seconds before each wafer polish. A 200 mm blanket copper wafer is polished for 20 seconds per wafer. In the first polishing recipe, the process wafer pressure and the retaining ring pressure are kept constant at 1.5 and 1.7 PSI, respectively, and the sliding speed is also kept constant at 0.5 m / s. In the second polishing recipe, the process wafer pressure and the retaining ring pressure are kept constant at 2.5 and 2.7 PSI, respectively, and the sliding speed is also kept constant at 1.6 m / s. The slurry flow rate is kept constant at 160 cc / min for both polishing recipes. Without sonication, the average copper removal rates are 5,703 and 15,552 Angstroms / min for the first and second polishing recipes, respectively. For the polishing process with slurry sonication, two sonicator bowls are used in parallel with a slurry flow rate of 80 cc / min per bowl, resulting in a total slurry flow rate of 160 cc / min. The sonic energy in each sonicator bowl is set to 2.0 Watts / cm. 2 With a setting of 0.05% and an incubation time of 5 minutes, the average copper removal rates increased to 7,397 and 19,383 Å / min for the first and second polishing recipes, respectively, representing a 30 and 25% increase in removal rate compared to the process without ultrasonic treatment.
[0124] In another example, a tungsten slurry, Versum Materials DP1236®, mixed with hydrogen peroxide (per manufacturer's specifications) is used. A Dupont IC1000® XY grooved pad on a 500 mm rotating platen is used. A Saesol 4DNS80AMC1 diamond conditioning disk is also used in ex-situ conditioning mode for 30 seconds before each wafer polish. A 200 mm blanket tungsten wafer is polished for 45 seconds per wafer. The process wafer pressure and the retaining ring pressure are kept constant at 3 and 6 PSI, respectively. The sliding speed is also kept constant at 1.6 m / sec. The slurry flow rate is kept constant at 80 cc / min. Without sonication, the tungsten removal rate is 3,197 Angstroms / min. For the polishing process with slurry sonication, two sonicator bowls are used in parallel with a slurry flow rate of 40 cc / min per bowl, resulting in a total slurry flow rate of 80 cc / min. Sonic energy in each sonicator bowl was set at 2.0 watts / cm 2 With a setting of 0.05% and an incubation time of 5 minutes, the average tungsten removal rate increased to 3,395 Å / min, representing a 6% increase in removal rate compared to the process without sonication.
[0125] While the above describes what is believed to be the best mode and / or other embodiments, it is understood that various modifications may be made therein and that the subject matter disclosed herein may be embodied in a variety of forms and examples, and that the present teachings may be applied to numerous applications, only a few of which are described herein. It is intended that the following claims claim all such applications, modifications, and variations that fall within the true scope of the present teachings.
Claims
1. 1. A chemical mechanical planarization (CMP) method comprising: (1) mixing an aqueous CMP slurry; (2) an encapsulating agent forming a supramolecular structure selected from the group consisting of vesicles, micelles, polyelectrolytes, and liposomes; and (3) a material additive selected from the group consisting of ligands, ligand-metal complexes, and non-metal reactive oxygen species (ROS) catalysts, thereby forming a modified slurry; applying at least one of mechanical wave energy or electromagnetic wave energy to the modified slurry, thereby forming an activated modified slurry; planarizing the substrate while the substrate is exposed to the activated modified slurry; The method includes:
2. The method of claim 1 , wherein the encapsulating agent is a poloxamer.
3. The method of claim 1 , wherein the encapsulating agent is an organic quaternary ammonium salt.
4. The method of claim 1 , wherein the encapsulating agent is selected from the group consisting of hydrogen trialkano ammonium salts and sulfate ester salts.
5. The method of claim 1 , wherein the encapsulating agent is a salt of a carboxylic acid having at least 10 carbons.
6. 2. The method of claim 1, wherein the encapsulating agent is selected from the group consisting of sorbitan esters and polyethylene glycol sorbitan esters.
7. 2. The method of claim 1, wherein the encapsulating agent is selected from the group consisting of alginate, chitosan, pectin, polydiallyldimethylammonium halide, polyethyleneimine, polyacrylic acid, polysodium 4-styrenesulfonate, poly(2-dimethylamino)ethyl methacrylate) methyl halide quaternary salt, poly(allylamine) hydrohalide, poly(diallyldimethylammonium halide).
8. The method of claim 1 , wherein the encapsulating agent is a phospholipid.
9. 10. The method of claim 1, wherein the material additive is a ligand having a water solubility of less than 20 grams per liter when measured at 22°C.
10. 10. The method of claim 1, wherein the material additive is a ligand having a water solubility of less than 10 grams per liter when measured at 22°C.
11. The method of claim 1 , wherein the material additive is a ligand that is a xanthine or hypoxanthine.
12. 2. The method of claim 1, wherein the material additive is a ligand selected from the group consisting of salicylhydroxamic acid (SHA), suberohydroxamic acid, tert-butyl N-(benzyloxy)carbamate, bipyridyl, lysine, tryptophan, phenylalanine, tyrosine, ethylacetohydroxamate, hydroxycarbamide, benzhydroxamic acid, trans-cinnamic acid, adipic acid, and caproic acid.
13. The method of claim 1 , wherein the material additive is a ligand that is a hydroxamic acid.
14. 2. The method of claim 1, wherein the material additive is a ligand that is a hydroxamic acid selected from the group consisting of salicylhydroxamic acid (SHA), suberohydroxamic acid, hydroxycarbamide, and benzohydroxamic acid.
15. The method of claim 1 , wherein the material additive is a ligand that is salicylhydroxamic acid (SHA).
16. The method of claim 1 , wherein the material additive is a ligand that is an amino acid.
17. 10. The method of claim 1, wherein the material additive is a ligand that is an amino acid selected from the group consisting of tryptophan and phenylalanine.
18. 10. The method of claim 1, wherein the material additive is a ligand metal complex having a metal ion selected from the group consisting of magnesium ions, calcium ions, barium ions, nickel ions, copper ions, zinc ions, strontium ions, iron ions, cobalt ions, titanium ions, vanadium ions, chromium ions, molybdenum ions, and manganese ions.
19. 20. The method of claim 18, wherein the ligand has a water solubility of less than 20 grams per liter when measured at 22°C.
20. 20. The method of claim 18, wherein the ligand is salicylhydroxamic acid (SHA).
21. The method of claim 1 , wherein the providing step provides mechanical wave energy.
22. 1. A chemical mechanical planarization (CMP) method comprising: (1) mixing an aqueous CMP slurry; (2) an encapsulating agent forming a supramolecular structure selected from the group consisting of vesicles, micelles, polyelectrolytes, and liposomes; and (3) a material additive selected from the group consisting of ligands, ligand-metal complexes, and non-metal reactive oxygen species (ROS) catalysts, thereby forming a modified slurry, wherein the material additive has a water solubility of less than 20 grams per liter when measured at 22° C.; providing mechanical wave energy to the modified slurry, thereby forming an activated modified slurry; planarizing the substrate while the substrate is exposed to the activated modified slurry; A method comprising:
23. 23. The method of claim 22, wherein the material additive is salicylhydroxamic acid (SHA) and the encapsulating agent is a poloxamer.
Citation Information
Patent Citations
Slurry for chemical and mechanical polishing (Cmp), method of producing semiconductor device, apparatus for producing semiconductor device and method of handling cmp slurry
JP2003113370A
Slurry for forming insoluble silicates during chemical-mechanical polishing
JP2003509855A
Non-polymeric organic particles for use in chemical-mechanical planarization
JP2007535118A
Slurry supplying device and method of polishing semiconductor wafer utilizing the same
JP2009290139A
Polishing liquid composition
JP2010016064A